2021
DOI: 10.3390/cancers13215285
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Particle Imaging: An Emerging Modality with Prospects in Diagnosis, Targeting and Therapy of Cancer

Abstract: Background: Magnetic Particle Imaging (MPI) is an emerging imaging modality for quantitative direct imaging of superparamagnetic iron oxide nanoparticles (SPION or SPIO). With different physics from MRI, MPI benefits from ideal image contrast with zero background tissue signal. This enables clear visualization of cancer with image characteristics similar to PET or SPECT, but using radiation-free magnetic nanoparticles instead, with infinite-duration reporter persistence in vivo. MPI for cancer imaging: demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 158 publications
1
17
0
Order By: Relevance
“…[82] MPI directly detects the iron oxide particle tracers and constructs 3D structures with exceptional contrast and temporal resolution. [83] The spatial resolution of MPI is at a millimeter scale. By increasing the intensity of the magnetic field gradient or fabricating the microrobot using paramagnetic materials with higher susceptibility, the spatial resolution will be improved.…”
Section: Mri and Mpimentioning
confidence: 99%
“…[82] MPI directly detects the iron oxide particle tracers and constructs 3D structures with exceptional contrast and temporal resolution. [83] The spatial resolution of MPI is at a millimeter scale. By increasing the intensity of the magnetic field gradient or fabricating the microrobot using paramagnetic materials with higher susceptibility, the spatial resolution will be improved.…”
Section: Mri and Mpimentioning
confidence: 99%
“…X-space reconstruction is performed without a precalibration step through velocity compensation and gridding the received instantaneous signal to the known FFP locations in three-dimensional (3D) space. The FFP commonly passes through the FOV on a Cartesian trajectory or Lissajous trajectory (Tay et al, 2021a).…”
Section: Imaging Modalitymentioning
confidence: 99%
“…They then observed that tumors almost disappeared (Du et al, 2019). The anisotropy and colloidal stability of particles also lead to the higher SAR of the new particle relative to feridex (Khurshid et al, 2015;Bauer et al, 2016;Reichel et al, 2020;Tay et al, 2021a).…”
Section: Combination With Magnetic Fluid Hyperthermiamentioning
confidence: 99%
“…Fifty years later, in 2010, MagForce AG company (Berlin, Germany) obtained European Union Regulatory Approval (10/2011) for its the Nanotherm ® therapy and later in 2013 started a clinical study in current glioblastoma with Nanotherm ® therapy at the Charité Hospital in Berlin. Recently, the FDA approved the Nanotherm ® therapy system for intermediate-risk prostate cancer [12,13].…”
Section: Introductionmentioning
confidence: 99%